PENGARUH STRATEGI E-MARKETING DAN VARIASI PRODUK TERHADAP MINAT BELI KONSUMEN - M.A Baidowi (JURNAL KOMPETITIF, 2021)
The purpose of this study was to determine the effect of E-Marketing Strategy and Product Variation on Consumer Purchase Interest in buying Herbal Products HNI HPAI BC 1 Palembang Branch. The variables used in this study, E-Marketing Strategy (X1), Product Variation (X2), Consumer Purchase Interest (Y). The population in this study were 75 customers of HNI HPAI BC 1 Palembang Branch who bought Herbal Products HNI HPAI BC 1 Palembang Branch. This type of research is quantitative. The analysis technique used is multiple linear regression, hypothesis testing using the F test and t test.         The regression results obtained the equation Y = 3.695 + 0.589 X1 + 0.299 X2. Which means that Consumer Purchase Interest is influenced by E-Marketing Strategies and Product Variations. The results of the F test obtain Fcount (480,870), meaning that there is an effect of E-Marketing Strategy and Product Variation simultaneously on Consumer Purchase Intention. The results of the t test for the E-Marketing Strategy variable obtained tcount (10.583), and the Product Variation variable obtained tcount (4.520), which means that the E-Marketing Strategy and Product Variation had a partial effect on Consumer Purchase Interest in buying Herbal Products HNI HPAI BC 1 Palembang Branch.